2020
DOI: 10.3390/ijerph17134642
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Musculoskeletal Abnormalities in Patients in Recovery from a Unilateral Rupture-Repaired Achilles Tendon

Abstract: The purpose of this study was to compare the inter-limb joint kinematics, joint moments, muscle forces, and joint reaction forces in patients after an Achilles tendon rupture (ATR) via subject-specific musculoskeletal modeling. Six patients recovering from a surgically repaired unilateral ATR were included in this study. The bilateral Achilles tendon (AT) lengths were evaluated using ultrasound imaging. The three-dimensional marker trajectories, ground reaction forces, and surface electromyography (sEMG) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Musculoskeletal modeling represents a valuable non-invasive tool to estimate the internal body loads, which could not be directly measured otherwise ( Vigotsky et al, 2019 ; Imani Nejad et al, 2020 ). Modeling estimates showed good agreement with experimentally measured quantities, such as joint loads from instrumented prostheses and muscle activations from EMGs ( Lund et al, 2012 ; Marra et al, 2014 ; De Pieri et al, 2018 , 2019 ; Lunn et al, 2020 ; Sun et al, 2020 ). Through conventional gait analysis and inverse dynamics, we are able to compute kinetic parameters such as net joint moments and joint powers, which provide us insight into the function of various muscle groups in healthy and pathological gait patterns ( Sloot and van der Krogt, 2018 ).…”
Section: Introductionmentioning
confidence: 58%
“…Musculoskeletal modeling represents a valuable non-invasive tool to estimate the internal body loads, which could not be directly measured otherwise ( Vigotsky et al, 2019 ; Imani Nejad et al, 2020 ). Modeling estimates showed good agreement with experimentally measured quantities, such as joint loads from instrumented prostheses and muscle activations from EMGs ( Lund et al, 2012 ; Marra et al, 2014 ; De Pieri et al, 2018 , 2019 ; Lunn et al, 2020 ; Sun et al, 2020 ). Through conventional gait analysis and inverse dynamics, we are able to compute kinetic parameters such as net joint moments and joint powers, which provide us insight into the function of various muscle groups in healthy and pathological gait patterns ( Sloot and van der Krogt, 2018 ).…”
Section: Introductionmentioning
confidence: 58%
“…46 A combined subject-specific musculoskeletal and foot-ankle complex finite element model was developed to provide potential information for the study purposes and clinical application. 47 The late stance phase of walking (60%-100%) was selected for the finite element analysis, the 60% of the stance phase was defined as initial push-off and the heel start to arise. The 80% moment during the push-off phase was selected as the target point for finite element analysis.…”
Section: Discussionmentioning
confidence: 99%
“…46 A combined subject-specific musculoskeletal and foot-ankle complex finite element model was developed to provide potential information for the study purposes and clinical application. 47…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2020) conducted a study of gait analysis in patients 2 years following the surgical suturing of AT. The authors found that a restraint of plantar flexion of the foot along with a greater deficit in muscle strength is responsible for plantar flexion of the foot on the operated side, resulting in the increased risk in knee injury during gait [ 23 ]. Jadacka et al (2017) [ 24 ] had similar conclusions as Sun et al (2020) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%